Management Of Inherited Property Left By Their Parents For The Heirs Of Minor Children - Alfikri, M.Hasby; Muhammad, Muhammad (Ipso Jure, 2024)
:  Heirs themselves have the meaning of people who at the time of death are in a marital relationship with the testator, are related by blood, are Muslim and are not prevented by law from becoming heirs. In the distribution of inheritance experts, there are also several indicators, the first of which is age, a child can manage his own inheritance when he reaches the age of 21 or is married.A custodial guardian is a person who in reality exercises custodial authority as a parent over a child. One of the concepts of having a custodial guardian is to protect the rights and fulfill the child's basic needs and manage the child's assets in order to ensure the child's growth and development and the best interests of the child.Becoming a foster carer cannot be done easily. Foster carers must have responsibilities and conditions that need to be met. One of them is that foster carers must ensure that the children they care for have their needs met both physically, emotionally and spiritually. Inheritance management refers to the processes and actions that regulate, manage and protect inheritance inherited from heirs, especially if the heirs are minors. This management must comply with applicable law, both civil law and Islamic law, which regulates guardianship and the rights and obligations of guardians in safeguarding the interests of children.